2003
DOI: 10.1080/15419060302062
|View full text |Cite
|
Sign up to set email alerts
|

Functional Effect of Contortrostatin, a Snake Venom Disintegrin, on Human Glioma Cell Invasion In Vitro

Abstract: The metastatic spread of cancer is a complex process that involves the combination of different cellular actions including cell adhesion to the extracellular matrix (ECM), breakdown of the ECM by specific matrix-degrading proteinases, and active cell locomotion. Contortrostatin (CN), a homodimeric snake venom disintegrin, has previously been demonstrated to be effective in blocking vitronectin/fibronectin-dependent adhesion and invasion of T98G human glioblastoma cells through Matrigel using in vitro studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…Studies employing cell lines have shown that contortrostatin can be effectively used in vitro in a number of cases [37], but there is no information about the effect of this drug in a primary culture of breast cancer cell where tumor cells retain their original phenotype. The results in our study are in agreement with data provided by other workers [27,35] and they extend our previous observations [25,38] on the use of RGD peptides in primary breast cancer cultures.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Studies employing cell lines have shown that contortrostatin can be effectively used in vitro in a number of cases [37], but there is no information about the effect of this drug in a primary culture of breast cancer cell where tumor cells retain their original phenotype. The results in our study are in agreement with data provided by other workers [27,35] and they extend our previous observations [25,38] on the use of RGD peptides in primary breast cancer cultures.…”
Section: Discussionsupporting
confidence: 94%
“…Snake venoms and hemostatic system have been under consideration in relation to the role of disintegrins in platelet aggregation [26]. The anti-invasive activity of contortrostatin has been studied using human glioblastoma cell lines [27] as well as its anti-tumor activity in Ehrich ascites carcinoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…Snake venom disintegrins are synthesized in vivo as multimodular proteins that comprise a signal peptide, a pro-domain, a metalloprotease domain, a disintegrin domain, and a cysteine-rich domain (Bjarnason and Fox, 1994;Fox and Serrano, 2005;Ramos and Selistre-de-Araujo, 2006). Recently, several disintegrins have been proposed as therapeutic drugs, in view of their antitumor, antiangiogenic and antithrombotic activities (Braud et al 2000;Matsui et al 2000;Zhou et al 2000;Schmitmeier et al 2003;Swenson et al 2004;Markland et al 2005;Yang et al 2005). For such applications, a few cDNAs encoding disintegrins, originally from snake venom glands, have been cloned and expressed both in bacteria and in insect cells (Park et al 1998;Fan et al 1999;Jeon and Kim, 1999;Wang et al 2003;Wang et al 2004) by genetic engineering techniques.…”
mentioning
confidence: 99%
“…Its toxic and side effects were unavoidable. Great efforts have been made [42][43][44][45] , but the problem remains unresolved. So a long-standing goal in snake venom therapy of cancer is to find a stable, low toxic, highly effective chemotherapeutic agent that selectively targets tumor cells.…”
Section: Discussionmentioning
confidence: 99%